1987
DOI: 10.1677/joe.0.1120215
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendocrine studies in hyperprolactinaemic male mice

Abstract: In several species, including man and the rat, hyperprolactinaemia is associated with suppression of gonadotrophin release and male sexual behaviour. However, in the hyperprolactinaemic male mouse, plasma LH and FSH levels and copulatory behaviour are increased rather than suppressed. In an attempt to identify mechanism(s) which may be responsible for these effects of hyperprolactinaemia in the mouse, we have examined the effects of two ectopic pituitary isografts on several indices of hypothalamic and pituita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

1988
1988
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…However, we do not believe that these differences in any way invalidate our conclusions. Two to five fold variations in the average values of plasma hormone levels in animals of the same strain, sex, and age sacrificed on differ ent occasions are characteristic of this species [22,24, and pre vious studies cited therein]. In spite of these differences, the ef fects of the hGH hybrid gene on plasma LH levels in males were consistent in three independent experiments with LH as says performed in two different laboratories [10, 11; Chandrashekar, Bartke and Wagner, unpubl.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, we do not believe that these differences in any way invalidate our conclusions. Two to five fold variations in the average values of plasma hormone levels in animals of the same strain, sex, and age sacrificed on differ ent occasions are characteristic of this species [22,24, and pre vious studies cited therein]. In spite of these differences, the ef fects of the hGH hybrid gene on plasma LH levels in males were consistent in three independent experiments with LH as says performed in two different laboratories [10, 11; Chandrashekar, Bartke and Wagner, unpubl.…”
Section: Discussionmentioning
confidence: 88%
“…Tire levels o f norepinephrine and dopamine in the median eminence and medial basal hypothalamus were measured by high-pres sure liquid chromatography (HPLC) with electrochemical detection, and turnover rates of these neurotransmitters were calculated from val ues determined in «-MPT-injected and noninjected animals within each group. These procedures were described in our previous publications [11,21], Tile levels of prolactin and LH in blood plasma, pituitary tis sue, and incubation media were quantitated by radioimmunoassays as described in our earlier publications [22] and expressed in terms of mouse AFP 6476C prolactin standard and rat LH RP-2 reference preparation.…”
Section: Studies O F Hypothalamic and Pituitary Functionmentioning
confidence: 99%
“…PRL is a polypeptide hormone that is synthesized and secreted from mammotropes in the anterior lobe of the pituitary gland [5]. Many studies have documented a critical role of PRL in the maintenance of lactation in women and female animals [6,7] as well as in immunregulation in both, males and females [8], however, its role in sexual behavior is not entirely clear [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The sudden depletion of the lipids and cholesterol at the height of the breeding activity has also been noted in a number reptilian species, and it has been suggested that it is probably indicative of rapid utilization of precursor material at a time of high androgen release (Loft, 1968).These reports are in agreement with our findings in the jungle crows. Annual reproductive cycle and cyclic variations in reproductive hormones those are associated with structural changes in the testicular tissues (Bartke et al, 1987;Sinha-Hikim et al, 1988). These cyclic changes are partially caused by alteration in the rate of androgen biosynthesis by Leydig cells.…”
Section: Resultsmentioning
confidence: 99%